Multiply Directed Moments in a Brahms Song: “Schön war, das ich dir weihte” (Op. 95, No. 7) - Melissa Hoag (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
Brahms’s song “Schön war, das ich dir weihte,” op. 95/7, offers a melancholy setting of a brief text by Georg Friederich Daumer. Several melodic disjunctions figure prominently in Brahms’s setting of the poem; in treating these disjunctions, normative voice-leading expectations are thwarted in ways that never meet satisfactory resolutions. Around these violations are crystallized the central expressive issues of the song, involving ambiguities not only in the domain of melody, but also of harmony, phrase structure, and form; this web of ambiguity is termed a “multiply directed moment.” Other issues in the song include the discursive phrase structure in the B section, as well as Brahms’s musical treatment of the subjunctive mood. Schenkerian analysis is used to explicate the unique melodic processes at work in Brahms’s setting, and the relationship of these melodic processes to Daumer’s text. The complex phrase structure of the middle section is also examined using a recompositional approach, which yields yet another level of interpretive insight. Nearly every parameter and time point in the song can be identified as multiply-directed; a spectrum of possible continuations or meanings is presented at every turn. Brahms’s setting thus focuses our attention on the multiply-directed moments in the song by meeting expectations with various levels of denial or surprise.